Pertussis seasonal variation in Northern Vietnam: the evidence from a tertiary hospital - Nhung TH Pham; Quyen TT Bui; Dien M Tran; Mattias Larsson; Mai P Pham; Linus Olson (BMC, 2024)
Abstract Background Pertussis is a highly contagious and dangerous respiratory disease that threatens children's health in many countries, including Vietnam, despite vaccine coverage. From 2015 to 2018, Vietnam experienced an increasing number of pertussis patients. Therefore, this study aimed to investigate the trend and examine the seasonal variations of pertussis in North Vietnam. Methods Data were collected from medical records of all under-5-year-old inpatients admitted to the National Children's Hospital in Hanoi, Vietnam (VNCH) 2015-2018. A descriptive analysis was performed to describe the distribution of incident cases by year and season. Linear multivariable regression was conducted to investigate the association between the incidence of cases and seasonality adjusted by age and vaccination status. Results We identified 1063 laboratory-confirmed patients during 2015-2018, including 247 (23.2%) severe patients. The number of pertussis patients admitted to VNCH per 1000 hospitalizations was 3.2 in 2015, compared to 1.9, 3.1, and 2.1 in 2016, 2017, and 2018, respectively. Outbreaks occurred biennially; however, there was no significant difference in the number of severe patients over this period. Most cases occurred in the hot season (509 patients, or nearly half of the study population). With the adjustment of the vaccination rate and average age, the risk of pertussis-associated hospitalization in the mild season and the hot season was 21% (95% CI [0.12; 0.3]) and 15% (95% CI [0.05; 0.25]) higher than that in the warm season, respectively. The rate of hospitalizations was high in the mild season (28.9%) and the warm season (30.8%), nearly twice as much as that in the hot season; nevertheless, the death rate was only striking high in the mild season, about 5-6 times as much as those in the other seasons. Conclusion The pertussis incidence in Northern Vietnam varied between seasons, peaking in the hot season (April-July). However, severe patients and deaths increased in the mild season (December-March). Interventions, for example, communication activities on pertussis and vaccination, are of immense importance in lowering the prevalence of pertussis. In addition, early diagnoses and early warnings performed by health professionals should be encouraged.